Sensitivity Analysis of Integrated Sensors Created Through Additive Manufacturing for Monitoring Components Subject to Dynamic Loads - Agnese Staffa; Massimiliano Palmieri; Giulia Morettini; Filippo Cianetti (Engineering Proceedings)
The progress in the development of sensors made using additive manufacturing (AM) techniques has opened up new possibilities for their integration into more complex structures, such as CubeSats. In this study, preliminary tests were conducted on printed sensors by FDM embedded in simple structures to evaluate their feasibility under simulated operational conditions, including temperature variations and dynamic loads. The results obtained represent a preliminary step toward the full integration of embedded sensors in 3D-printed structures. With further development, 3D-printed embedded sensors could be used to monitor dynamic loads and vibrations during service, which is essential for structural health monitoring and determining fatigue life.